2009
DOI: 10.1097/gim.0b013e31819c6b2d
|View full text |Cite
|
Sign up to set email alerts
|

Retention of medical genetics knowledge and skills by medical students

Abstract: Purpose: To determine whether specific knowledge and skills medical students acquire after completing a Year 1 genetics course are retained at the end of Year 3. Methods: A genetics case was developed for an observed structured clinical exam at the end of Year 3. The case involved a pregnant patient who underwent population screening for cystic fibrosis and is identified as a carrier of a common mutation. Student's performance in completing eight essential genetic tasks taught in Year 1 was assessed by their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…Greb et al have re por ted that third ye ar me di cal stu dents do not re ta in me di cal ge ne tics know led ge and skills le ar ned in the first ye ar of me di cal school. 15 In anot her study, Eng ler et al as ses sed in tervi e wing and com mu ni ca ti on skills of me di cal stu dents just af ter a re le vant co ur se and one ye ar la ter. 16 They fo und a sig ni fi cant dec li ne in stu dent pro cess-ori en ted skills, and conc lu ded that ef fec tive in ter vi e wing and com mu ni ca ti on skills can be not only le ar ned but al so for got ten.…”
Section: Discussionmentioning
confidence: 99%
“…Greb et al have re por ted that third ye ar me di cal stu dents do not re ta in me di cal ge ne tics know led ge and skills le ar ned in the first ye ar of me di cal school. 15 In anot her study, Eng ler et al as ses sed in tervi e wing and com mu ni ca ti on skills of me di cal stu dents just af ter a re le vant co ur se and one ye ar la ter. 16 They fo und a sig ni fi cant dec li ne in stu dent pro cess-ori en ted skills, and conc lu ded that ef fec tive in ter vi e wing and com mu ni ca ti on skills can be not only le ar ned but al so for got ten.…”
Section: Discussionmentioning
confidence: 99%
“…Most have important deficiencies in their knowledge of genetics and genetic tests [73], and most medical students do not retain the genetics education they received [74,75]. It would therefore be unrealistic to presume that most clinicians will be able to integrate new genetic tests into their practice based on their assessment of the evidence.…”
Section: Benefits Of Defining the Issuesmentioning
confidence: 99%
“…However, it has been demonstrated that medical students do not to retain genetics knowledge over the course of their medical school career (Baars et al 2005;Greb et al 2009;Ling et al 2008;Swanson et al 1996). Retention of knowledge regarding genetics may be further eroded by the fact that PCPs are more likely to see patients with common conditions such as heart disease or diabetes than those who have single gene disorders (Feero 2005).…”
Section: Introductionmentioning
confidence: 99%